Leg stiffness and joint stiffness while running to and jumping over an obstacle - Mauroy, G.; Schepens, B.; Willems, P. A. (Journal of Biomechanics, 2014)
During running, muscles of the lower limb act like a linear spring bouncing on the ground. When approaching an obstacle, the overall stiffness of this leg-spring system (kleg) is modified during the two steps preceding the jump to enhance the movement of the center of mass of the body while leaping the obstacle. The aim of the present study is to understand how kleg is modified during the running steps preceding the jump. Since kleg depends on the joint torsional stiffness and on the leg geometry, we analyzed the changes in these two parameters in eight subjects approaching and leaping a 0.65m-high barrier at 15kmh-1. Ground reaction force (F) was measured during 5-6 steps preceding the obstacle using force platform and the lower limb movements were recorded by camera. From these data, the net muscular moment (Mj), the angular displacement (Thetaj) and the lever arm of F were evaluated at the hip, knee and ankle. At the level of the hip, the Mj-?j relation shows that muscles are not acting like torsional springs. At the level of the knee and ankle, the Mj-Thetaj relation shows that muscles are acting like torsional springs: as compared to steady-state running, the torsional stiffness kj decreases from ~1/3 two contacts before the obstacle, and increases from ~2/3 during the last contact. These modifications in kj reflect in changes in the magnitude of F but also to changes in the leg geometry, i.e. in the lever arms of F.